1999
DOI: 10.1111/j.1600-0536.1999.tb06178.x
|View full text |Cite
|
Sign up to set email alerts
|

Colophony allergy: a review

Abstract: Colophony is a complex mixture of over 100 compounds derived from pine trees. It has countless applications at home and at work and exposure to colophony and modified-colophony is universal. It is the oxidation products of unmodified and modified colophony and some of the new resin acids synthesized during modification that are the principle allergens in colophony. The neutral fraction may account for a small % of positive reactions. When screening for allergy using unmodified gum rosin, allergy to modified ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 65 publications
2
77
0
1
Order By: Relevance
“…Decarboxylation of resin acids may also take place. In consequence, the composition of free or esterified resin acids in GETOR or GEWR is expected to differ from that of the parent rosins TOR or wood rosin, respectively (Soltes and Zinkel, 1989;Downs and Sansom, 1999). Table 4 compares the resin acids present in TOR, wood rosin and gum rosin.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…Decarboxylation of resin acids may also take place. In consequence, the composition of free or esterified resin acids in GETOR or GEWR is expected to differ from that of the parent rosins TOR or wood rosin, respectively (Soltes and Zinkel, 1989;Downs and Sansom, 1999). Table 4 compares the resin acids present in TOR, wood rosin and gum rosin.…”
Section: 6mentioning
confidence: 99%
“…Dermal contact sensitisation is seen with different types of rosins and modified rosins and their components as well as with GETOR, GEWR, and GEGR (e.g. Downs and Sansom, 1999;Gaefvert et al, 1994;Hausen and Mohnert, 1989;Shao et al, 1993;Geier and Hausen, 2006). Even though it was not possible to sensitise guinea pigs to purified abietic acid (Karlberg et al, 1985), Hausen and Mohnert (1989) found that of 44 dermatologic patients, 17 (39%) reacted positively to purified abietic acid as well as to standard rosin in a patch test.…”
Section: 26mentioning
confidence: 99%
“…Dermal contact sensitisation is seen with different types of rosins and modified rosins and their components as well as with GEGR, GEWR, and GETOR (e.g. Downs and Sansom, 1999, Gaefvert et al, 1994, Hausen and Mohnert, 1989Shao et al, 1993;Geier and Hausen, 2006;Illing et al, 2009). …”
Section: Other Studies/contact Sensitisationmentioning
confidence: 99%
“…No significant associations in either dentitions were found with baseline caries There was little information available on possible adverse effects or acceptability of treatment. As some of the varnishes have colophony (or rosin -a sticky substance obtained from conifers) as a component which is a known allergen, 9 it is important that new studies should be better at the reporting of adverse effects, although to date, only one case in an adult appears to have been reported in the literature. 10 …”
Section: Risk Of Bias Assessment Was Undertakenmentioning
confidence: 99%